2021
DOI: 10.3389/fmolb.2021.686086
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Crosstalk Among PTMs Provides Novel Insight Into the Structural Basis Underlying the Differential Effects of Nt17 PTMs on Mutant Httex1 Aggregation

Abstract: Post-translational modifications (PTMs) within the first 17 amino acids (Nt17) of the Huntingtin protein (Htt) have been shown to inhibit the aggregation and attenuate the toxicity of mutant Htt proteins in vitro and in various models of Huntington’s disease. Here, we expand on these studies by investigating the effect of methionine eight oxidation (oxM8) and its crosstalk with lysine 6 acetylation (AcK6) or threonine 3 phosphorylation (pT3) on the aggregation of mutant Httex1 (mHttex1). We show that M8 oxidat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 75 publications
2
20
0
Order By: Relevance
“…For instance, Nguyen et al, 2016, concluded that glutamine triggers acetylation-dependent degradation of glutamine synthetase, whereas Son et al, 2020, demonstrated that leucine regulates autophagy through acetylation of the mTORC1. , Moreover, the role of methionine involvement in lysine acetylation is not studied so far in AD and PD, but yet at the same time demonstrated the potential relationship between methionine and lysine acetylation in other neurological defects. For instance, Chiki et al, 2021, concluded that the presence of oxidation of methionine at position 8 and acetylation at K6 resulted in the dramatic inhibition of Httex1 fibrilization . Thus, these studies correlate with our results and suggest that glutamic acid (E), leucine (L), methionine (M), valine (V), and glutamine (Q) could be critical amino acid residues in acetylation and HDAC binding.…”
Section: Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, Nguyen et al, 2016, concluded that glutamine triggers acetylation-dependent degradation of glutamine synthetase, whereas Son et al, 2020, demonstrated that leucine regulates autophagy through acetylation of the mTORC1. , Moreover, the role of methionine involvement in lysine acetylation is not studied so far in AD and PD, but yet at the same time demonstrated the potential relationship between methionine and lysine acetylation in other neurological defects. For instance, Chiki et al, 2021, concluded that the presence of oxidation of methionine at position 8 and acetylation at K6 resulted in the dramatic inhibition of Httex1 fibrilization . Thus, these studies correlate with our results and suggest that glutamic acid (E), leucine (L), methionine (M), valine (V), and glutamine (Q) could be critical amino acid residues in acetylation and HDAC binding.…”
Section: Results and Discussionsupporting
confidence: 88%
“…For instance, Chiki et al, 2021, concluded that the presence of oxidation of methionine at position 8 and acetylation at K6 resulted in the dramatic inhibition of Httex1 fibrilization. 106 Thus, these studies correlate with our results and suggest that glutamic acid (E), leucine (L), methionine (M), valine (V), and glutamine (Q) could be critical amino acid residues in acetylation and HDAC binding. Further, structural information of CREB reveals that it consists of 11 exons and three isoforms that are produced through alternative splicing.…”
Section: Glutamic Acid and Leucine Predominatelysupporting
confidence: 89%
“…N-terminal HTT encoded by exon 1 has been found to be important for membrane anchoring, protein interactions, and subcellular distribution (Michalek et al, 2013 ; Tao et al, 2019 ; Riguet et al, 2021 ). In the exon 1 domain of HTT, the first 1–17 amino acids can modulate mutant HTT oligomerization, toxicity, and subcellular localization (Cornett et al, 2005 ; Gu et al, 2009 ; Arndt et al, 2019 ; Chiki et al, 2021 ; Vieweg et al, 2021 ). However, our findings showed that removing exon 1 of mouse Htt did not significantly alter its subcellular distribution.…”
Section: Discussionmentioning
confidence: 99%
“…N17 amino acids in exon 1 are well conserved across species and are thought to be important for HTT's function as well as the toxicity of mutant HTT. In support of this, N17 amino acids can markedly modify the toxicity of mutant HTT and its nuclear localization (Cornett et al, 2005;Gu et al, 2009;Arndt et al, 2019;Chiki et al, 2021;Vieweg et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…10 Therefore, a method to accurately identify protein PTMs is essential as increasing evidence suggests the PTM code is combinatorial in nature and involves complex interplay and cross-talk among PTMs. 11,12 PTMs have been implicated in a wide variety of diseases, such as characterizing the changes in protein PTM types and levels is highly relevant for early diagnosis and monitoring the progression of diseases, as well as for evaluating the efficacy of emerging therapies. 4,13 For example, several neurodegenerative diseases including Alzheimer's disease (AD) and Parkinson's disease (PD) are caused by the accumulation of misfolded and aggregated proteins in the brain regions that are affected by the disease (e.g., amyloid-β in amyloid plaques, Tau in neurofibrillary tangles, and α-synuclein in Lewy bodies and Lewy neurites).…”
mentioning
confidence: 99%